Analisis Perlindungan Hukum Hak Cipta Dalam Industri Game: Studi Kasus Mobile Legends dan League Of Legends - Syakilah Wanda Ramatasita; Agri Chairunisa Isradjuningtias (PT. Hasba Edukasi Mandiri, 2025)
This research examines the legal aspects of copyright protection within the online gaming industry. The rapid growth of the gaming sector has introduced significant intellectual property challenges, especially concerning the protection of creative elements such as character designs, music, storyline, and game mechanics. The study aims to analyse whether current copyright laws in Indonesia sufficiently protect online games and identifies juridical barriers in enforcing these rights. Using a normative juridical method, this research reviews existing regulations, literature, and judicial decisions to evaluate the effectiveness of copyright protection in the gaming industry and suggests improvements to strengthen intellectual property rights enforcement.